2004
DOI: 10.1007/s10194-004-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Dysimmune disorders and migraine: is there a possible common denominator?

Abstract: The association between headache, especially migraine, and some immunomediated diseases, in particular autoimmune diseases, is well known. The evidence in favor of this association comes prevailingly from epidemiological studies, as well as research aimed at assessing the onset and the course of migraine in relation with the onset and activity and the biological markers of autoimmune diseases. The most relevant findings in this regard concern celiac disease, systemic lupus erythematosus, and multiple sclerosis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The association between migraine and ischemic stroke has been well established, 21,22 and several studies have linked migraine attacks with abnormalities of platelet morphology and function and also with coagulation disorders. [23][24][25][26] Some studies have shown a reduction in migraine attacks with the use of anticoagulation or antiplatelet (clopidogrel) therapy in specific subsets of patients, 20,26 but 2 randomized studies failed to demonstrate a significant effect of warfarin or clopidogrel on migraine attacks. 27,28 The present study showed that in the presence of a specific trigger, clopidogrel may be highly effective in the prevention of migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between migraine and ischemic stroke has been well established, 21,22 and several studies have linked migraine attacks with abnormalities of platelet morphology and function and also with coagulation disorders. [23][24][25][26] Some studies have shown a reduction in migraine attacks with the use of anticoagulation or antiplatelet (clopidogrel) therapy in specific subsets of patients, 20,26 but 2 randomized studies failed to demonstrate a significant effect of warfarin or clopidogrel on migraine attacks. 27,28 The present study showed that in the presence of a specific trigger, clopidogrel may be highly effective in the prevention of migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of increased platelet aggregation following ASD closure has been demonstrated, 29 and this may have increased the release of substances such as serotonin or proinflammatory cytokines like interleukins 1, 6, and 8 and tumor necrosis factor α, which have been linked to migraine attacks. [23][24][25] Apart from its antiplatelet effects, clopidogrel has also proven antioxidant and anti-inflammatory properties. 30 Several studies have also shown improved endothelial function and nitric oxide bioavailability with the use of clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Through the neurovascular effects of chronic inflammatory processes on the brain, migraine has been reported in certain infectious diseases, such as Helicobacter pylori (HP) (20,21) and human immunodeficiency virus (HIV) infections (22,23), and certain autoimmune disorders, such as multiple sclerosis (MS) (24,25) and systemic lupus erythematosus (SLE) (25,26). The pathogenic effect of chronic inflammation on the brain is considered as an evidenced mechanism in the pathogenesis of migraine (5,6,8).…”
Section: Study Patientsmentioning
confidence: 99%
“…Chronic Osteomyelitis and Migraine several infectious diseases, such as HP (20,21) and HIV infections (22,23), and certain autoimmune disorders, such as MS (24,25) and SLE (25,26), could increase the risk of migraine. With an advantage of the availability of a large patient population extracted from the Taiwan NHIRD, we investigated whether patients with COM, a condition characterized by continuous, chronic, and severe inflammation, had higher risk of migraine.…”
Section: E153mentioning
confidence: 99%